Aspectos ambientais, parâmetros produtivos e nutricionais da Urochloa decumbens em sistema silvipastoril com diferentes arranjos - Claudinei Alves dos Santos (2018)
The objective of this paper was to evaluate the productivity and bromatological composition of Urochloa decumbens (signalgrass), the luminosity in understory and the chemical parameters of the soil in silvopastoral system (SPS) in Cerrado region. The experiment was carried in the Experimental field of Santa Rita/Epamig in the municipality of Prudente de Morais, Minas Gerais State, latitude 19°27'15'' South and longitude 44°09'11'' West. The experimental area was composed of a SPS in double line arrangements [(3x2) + 20m and 9x2m)] and simple line (9x2m) with three cultivares of Eucalyptus spp. (GG100, I144 and VM58) deployed in 2008. As a control treatment, two pastures were used in adjacent areas to the SPS, one with fertilization application and another without. The signalgrass productivity in the SPS was higher in the (3x2) + 20m arrangement. The productivity in the SPS was 58.6% [(3x2) + 20m], 85.6% [(2x2) + 9m] and 80.4% (9x2m) lower compared to the showed in pasture under fertilization. The percentage of senescent material in signalgrass dry matter was higher in the pastures under full sun. Higher protein levels and lower of dry matter, neutral detergent fiber (NDF) and acid detergent fiber (ADF) were obtained in the SPS. Crude protein (CP), NDF, ADF, hemicellulose and cellulose showed an arrangement effect for whole plant. The signalgrass performance did not vary in the SPS due the cultivar used in the integration. However, the leaf area index (LAI) as well as photosynthetically active radiation (PAR) were lower in the SPS with the I144 cultivar. In relation to the chemical parameters of the soil there was no effect for spatial arrangement of the SPS and for site evaluated (center of interrow or under the canopy trees) the carbon stock did not vary as to the arrangement and location in the parcel and showed an increase of 37.8% between the 3rd and the 7th year.